Nutrient management for fodder oats in India - An overview - Maragatham, N.; Gopalan, A. (MTT, 2004)
In India oats can be grown as fodder crops on all soils, apart from alkaline or waterlogged conditions, in all regions where wheat and barley are grown. It is mostly grown as winter crop. In addition, oats are quick growing, palatable, succulent and nutritious and acceptable to all categories of livestock. It can be fed in many forms such as green forage, straw, silage, and grains. With the introduction of new management systems (proper amounts of manure and fertilizers, multicut cultivars, better combinations such as oats + vetch and oats + peas) both commercial dairy farmers and resource-poor farmers have greatly reduced the feed shortage problem during the dry winter months as well as achieving a 30% reduction in the cost of feed. Besides growing fodder oats as sole crop, oats + vetch is the best mixture for high yields and improved soil fertility. For resource-poor farmers, oat cultivars Canadian and Kent are recommended and a combination of oats + vetch. The general nutrient management practice is application of FYM at the rate of 5 ton/ha by broadcast uniformly and another ploughing done. 80:60:40 kg ( N: P2O5: K20) is the recommended fertilizer rate, where N was used in three split doses, applied after each cut under irrigated conditions. Otherwise it was applied as one basal dose under rainfed conditions. After sowing, a land leveler was used to ensure good seed contact with soil. To optimize the fertilizer requirement, various trials were conducted under All India Coordinate Fodder Research Project. Application of 120 kg/ha resulted higher green fodder yield of 30 t/ha. To get a maximum possible yield application of 60 kg Sulphur/ ha along with recommended dose of fertilizer can be restored. Fodder oats is also cultivated in cropping sequences like Rice-Cowpea-oats and ricesorghum- oats. Application of 75 % of recommended fertilizer along with FYM (5 t/ha) recorded maximum rice equivalent yield of 40 t/ha in the case of rice-cowpea-oats cropping sequence. So, oats has the potential to serve as an important winter fodder crop in India during winter season. With good nutrient management it can potentially provides more and better fodder from the same unit of land than the traditionally grown winter wheat.
Keywords: Ka; mixture; vetch; feed; fertilizer; cropping system